The prospects and challenges of E- Government Procurement (E-GP) in Bangladesh- a case study on Public Works Department (PWD). - Hossain, Sazzad (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.